Ping pong : an exergame for cognitive inhibition training - Zhang, Hao (2021)
Cognitive inhibition, a key constituent of healthy cognition, has been shown to be susceptible to age-related cognitive declines. Research has shown that cognitive rehabilitation training can facilitate older adults to maintain healthy cognitive functions. Compared to cognitive rehabilitation alone, the combination of physical and cognitive exercises is more effective to train older adults’ cognitive functions. Focusing on the training of older adults’ cognitive inhibition, we design the Ping Pong exergame in this work, which incorporates the traditional cognitive task with physical exercises in the game environment to improve older adults’ cognitive inhibition. A longitudinal study was conducted to evaluate the usability of Ping Pong exergame and its effectiveness on training older adults’ cognitive inhibition. The results show that the Ping Pong exergame received a good usability score and players presented significantly better performance in cognitive tasks after playing the exergame.